2003
DOI: 10.1038/sj.ijo.0802406
|View full text |Cite
|
Sign up to set email alerts
|

Moderate physical activity permits acute coupling between serum leptin and appetite–satiety measures in obese women

Abstract: OBJECTIVES:To investigate whether moderate physical activity or snack intake influence appetite sensations and subsequent food intake in obese women. Associations between serum leptin and appetite ratings were also investigated. METHODS: In all, 10 obese women (mean age7s.d.: 50.078.5 y; mean body mass index (BMI)7s.d.: 37.276.5 kg m À2 ) were submitted in random order to three trials: Moderate physical activity (20 min brisk walking), Snack (58.5 g chocolatebased) and Control (sitting, TV-watching). Appetite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 51 publications
5
58
1
Order By: Relevance
“…The use of male participants in the majority of investigations has led some authors to postulate that sex-based differences may occur in the appetite response to exercise due to the critical relationship between energy balance and reproductive function in females (38) . However, the present research suggests that females do not exhibit increased appetite perceptions during the 2 h period after exercise (18,19,29,(31)(32)(33) . Furthermore, a recent study by Hagobian et al (29) directly compared the appetite response to exercise in male and female participants and concluded that 80 min cycling at 70 % VO 2 max did not stimulate increases in appetite in either sex during the 40 min after exercise.…”
Section: Exercise-induced Anorexiamentioning
confidence: 57%
See 4 more Smart Citations
“…The use of male participants in the majority of investigations has led some authors to postulate that sex-based differences may occur in the appetite response to exercise due to the critical relationship between energy balance and reproductive function in females (38) . However, the present research suggests that females do not exhibit increased appetite perceptions during the 2 h period after exercise (18,19,29,(31)(32)(33) . Furthermore, a recent study by Hagobian et al (29) directly compared the appetite response to exercise in male and female participants and concluded that 80 min cycling at 70 % VO 2 max did not stimulate increases in appetite in either sex during the 40 min after exercise.…”
Section: Exercise-induced Anorexiamentioning
confidence: 57%
“…In accordance with the appetite responses detailed in the previous section, the majority of these studies demonstrated that energy intake was unaffected by exercise (27)(28)(29)(30)32,33,(39)(40)(41) . However, some studies have demonstrated increases (18,19,37,42) or decreases (34,43,44) in energy intake after exercise.…”
Section: Energy Intake Responses In the Immediate Post-exercise Periomentioning
confidence: 67%
See 3 more Smart Citations